Size-Controlled Nanoparticle Clusters of Narrow Size- Polydispersity Formed Using Multiple Particle Types Through Competitive Stabilizer Desorption to a Liquid– Liquid Interface - Fox, Eoin K.; El Haddassi, Fadwa; Hierrezuelo Osorio, Jose Manuel; Ninjbadgar, T.; Stolarczyk, Jacek K.; Merlin, Jenny; Brougham, Dermot F. (Wiley, 2018)
A novel colloidal approach is presented for preparing fully dispersed nanoparticle (NP) assemblies (clusters) of narrow size-polydispersity over a wide range of sizes through irreversible depletion of stabilizing ligands onto a liquid–liquid interface. Unusually, the relative monodispersity of the assemblies continuously improves throughout the process. A detailed kinetics study into the assembly of iron oxide NP clusters shows that the assembly rate decreases with NP concentration, pinpointing the role of the interface in size focusing. A new protocol for identifying initial conditions that enable controlled assembly is described, which allows extension of the approach to multiple NP types, opening up a general route to colloidally processed materials. The process uses cheap materials, it is reproducible, robust, and scaleable, and it allows for selection of both particle and cluster size. In the case of assemblies of magnetic iron oxide NPs, these advantages enable tuning of the magnetic properties of the assemblies for applications such as magnetically targetable MRI-trackable agents in biomedicine.
Keywords: Nanopartículas; nanoparticles; Polydispersity; Competitive Stabilizer Desorption; Clusters